IDENTIFIKASI KESALAHAN SISWA DALAM MENGERJAKAN SOAL BANGUN RUANG SISI DATAR - Fawaid, Abdul Husnan; Sulisawati, Dwi Noviani; Hidayatin, Nur (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This study was conducted to identify errors made by 38 ninth-grade students of MTs Ar Riyadh Jenggawah in solving problems of flat-sided solid geometry. The instruments used were test results and interviews. Of the 38 students who took the test, the researcher took three as research subjects. The three subjects were taken based on the results of the students' work. Students experienced errors in solving problems of flat-sided solid geometry, including conceptual errors, procedural errors, and technical errors. Conceptual errors where students made errors when determining a formula, procedural errors where students made errors by not using the steps of the work, and technical errors where students made errors by determining an operation symbol. Based on the results of the analysis, the most common errors made by students were students unable to determine the formula and how to work on it.